If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 4y + 11 + -2 Reorder the terms: 15 = 11 + -2 + 4y Combine like terms: 11 + -2 = 9 15 = 9 + 4y Solving 15 = 9 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 15 + -4y = 9 + 4y + -4y Combine like terms: 4y + -4y = 0 15 + -4y = 9 + 0 15 + -4y = 9 Add '-15' to each side of the equation. 15 + -15 + -4y = 9 + -15 Combine like terms: 15 + -15 = 0 0 + -4y = 9 + -15 -4y = 9 + -15 Combine like terms: 9 + -15 = -6 -4y = -6 Divide each side by '-4'. y = 1.5 Simplifying y = 1.5
| 6-4(2-5x)=6-4(-3x) | | 7x-8=14x+8 | | 450-1000=x | | x-3x=3 | | 3x+1+4x-5= | | 143/7= | | 2y+4z=8 | | -1-n=5 | | F(2)=(2)+7 | | 12+5w-4w=5 | | 4+(s+2s)-s=2s-1(12) | | 4(6w+4)*(5-3)=5(3w+9)*4(6w+8) | | 45(-d)=79 | | F(1)=(1)+7 | | y^2+x^2+8y-10x+37=0 | | 3x+x-4=12 | | 54x-7+x=36 | | 3x+x-4=6 | | n-3n=20-4n | | 36+-4c+-3c=22 | | 10x+x-2=-90 | | 5n+(-6)=-2 | | 36-4v-3c=22 | | (3-4x)-3(2.4x-7)= | | x+8=6x+3 | | -17x=-12 | | 5+4x=x-6 | | 2753-3456+13= | | 2(x-7)=327 | | 2nm+5=3 | | 8(y+5)=y(10) | | 6x^2+9=33 |